Does green re-industrialization pay off? Impacts on employment, wages and productivity - Federico Fabio Frattini; Francesco Vona; Filippo Bontadini (Fondazione Eni Enrico Mattei (FEEM), 2024)
What are the consequences of green industrialization on the labour market and industry dynamics? This paper tackles and quantifies this question by employing observable and reliable data on green manufacturing production for an extensive set of EU countries and 4-digit manufacturing industries for over a decade. First, at a descriptive level, this paper documents that potentially green industries outperform the others in terms of employment, average wages, value added and productivity, net of controlling for other drivers of the labour market and industry dynamics. Second, employing a shiftshare instrument to purge the analysis from possible endogeneity within green potential industries, this paper finds that an expansion of green production implies an increase in employment and value added. In contrast, average wages and labour productivity remain unchanged. These results hold in the short and long term, are heterogeneous depending on the countries considered, and are amplified by existing industry specialization and by accounting for input-output linkages.
Keywords: J21; J31; L6; O14; 330; Green transition; Employment; Manufacturing; Shift-share